2013
DOI: 10.1007/s11999-012-2721-9
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity Does Not Imply Poor Outcomes in Asians after Total Knee Arthroplasty

Abstract: Background In Asia, obesity has reached epidemic proportions and physicians are likely to face a burden of obesity-related disorders, of which osteoarthritis of the knee is one. However, it is unclear whether obesity affects improvement of conventional TKAs in Asian patients. Purpose We therefore asked whether obese patients with a BMI of 30 kg/m 2 or greater would have worse ROM and function after TKA compared with their nonobese counterparts and whether they would have less improvement preoperatively to post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
2
29
1
4
Order By: Relevance
“…There have been conflicting studies regarding the association of morbid obesity with increases in short-term and long-term complications after TKA [3,6,10,13,14,16,18,19,[23][24][25]. Multivariate analyses to determine specifically whether morbid obesity alone or other comorbid conditions such as malnutrition are the primary factors associated with the increased risk of complications were not performed in some of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been conflicting studies regarding the association of morbid obesity with increases in short-term and long-term complications after TKA [3,6,10,13,14,16,18,19,[23][24][25]. Multivariate analyses to determine specifically whether morbid obesity alone or other comorbid conditions such as malnutrition are the primary factors associated with the increased risk of complications were not performed in some of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of TKA in populations at greater risk for complications are less well defined. Morbid obesity and malnutrition have been shown to be associated with increased perioperative complications after TKA [5,6,10,12,16,18,19,27,32]; however, some studies have not shown an increased risk of perioperative complications in patients who are morbidly obese [3,13,14,23,25]. In addition, patients with morbid obesity are more likely to be malnourished than patients who are not obese, raising the question whether morbid obesity, malnutrition, or both, are independently associated with increased perioperative complications [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Констатировано, что ожирение несомненно раньше приводит к необходимости радикальных вмешательств по поводу остеоартроза, а клинико-функциональ-ные результаты в раннем послеоперационном периоде статистически значимо хуже у тучных пациентов [31]. При этом, пери-и послеопера-ционные осложнения были схожи как по форме, так и по количеству в рецензируемых группах [13][14][15].…”
Section: ожирение и радикальный подход в лечении остеоартритаunclassified
“…Previous studies have shown that a high BMI is associated with the risk of TKR failure, with regard to both clinical outcome and quality-of-life indicators (12)(13)(14)(15). However, other studies have shown that BMI is not associated with post-TKR outcomes (16,17). Mizner et al showed that both performance-based mobility tests and self-report questionnaires are required for the reliable assessment of short-term post-TKR outcomes (18).…”
Section: Introductionmentioning
confidence: 99%